SYNTHESIS, INFRARED AND NMR STUDIES OF SOME SULFATO DIORGANOSTANNIC DERIVATIVES - DAOUDA NDOYE; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
EthylendiammoniumSO4•SnBu2Cl2•1/4ethylendiammoniumCl2 (A), 2ethylendiammoniumSO4•SnBu2Cl2 (B) and Cy2NH2SO4H•Cy2NH2SnBu2Cl3 (C) complexes have been obtained on allowing ethylendiammoniumSO4 and Cy2NH2HSO4 to react respectively with SnBu2Cl2 in specific ratios. The molecular structures of these compounds have been determined on the basis of infrared and NMR data. The suggested structures are dimeric and tetrameric, the tin atom being hexacoordinated, the sulphate anions behaving as a monochelating ligand or non-coordinating and only involved in hydrogen bonds. The hydrogenosulfate is a non-sigma coordinating anion but only involved in hydrogen bonds of acetic acid type or NH…O bonds. The presence of dimeric [(SnBu2Cl3)2]2- in one of the structures is noteworthy. The key role of the cations involved in hydrogen bonds is outlined.